Human rights and democracy promotion : reflections on the contestation in, and the politico-economic dynamics of, rights promotion - Kurki, Milja (2011)
Examines from the theoretical perspective the nature of the relationship between human rights and promotion of democracy. Argues that these are inherently contradictory in nature and calls for a more politicised and openly contradiction-accepting approach to rights and democracy promotion.